(untitled) (Journal of Comparative & International Higher Education, 2024)
With the onslaught of the COVID-19 pandemic, Japanese higher education (HE) began the process of full digitalization in the academic year 2020. Considering that Japanese HE was previously dominated by face-to-face learning, the efforts of the stakeholders to implement digitalization deserve praise. However, digitalization has shown varying degrees of progress, both in terms of the type of education and between and within organizations. This study investigates the status of HE digitalization in Japan by focusing on the policy measures of the central government, the teaching and learning by faculties and students who are the traditional bearers of education, and the concept of lifelong learning and continuing education, which is exponentially attracting attention as a new area of study. This research also examines how those involved can use digitalization to improve HE and the goals and challenges of the transformation. Although the measures against the impact of the pandemic on the education sector greatly improved the digitalization of education in universities, other essential issues for educational reform became apparent. To take full advantage of the benefits of digitalization, it is necessary to re-examine the factors that hinder it, such as the changes in awareness among stakeholders, and take immediate measures to address them. In this context, dialogue is extremely important. The stakeholders should discuss how digitalization can enhance the value of university education.